1,2-diacetals: a new opportunity for organic synthesis. - Ley, S; Baeschlin, D; Dixon, D; Foster, A; Ince, S; Priepke, H; Reynolds, D (ACS, 2001)
The use of 1,2-diacetals for a number of synthetic applications to provide diol protection and reactivity control was studied. The chiral versions of these systems were used to desymmetrize the enantiotopic diol pairs and to discriminate diequatorial diols in many carbohydrate derivatives. The fusion of these rigid units to the carbohydrate substrates proved effective for tuning the reactivity during glycosidic coupling reactions. The studies confirmed that the methyl groups acted as useful diagnostic markers to analyze the nuclear magnetic resonance features of the compounds.